Kauthar: an anthology of the speeches of Imam Khomeini (s.a.) including an account of the events of the revolution from 1962-1978 - Kauthar... (The Institute for Compilation and Publication of the Works of Imam Khomeini International Affairs Divition, 1995)
st,1/WS.C.1